1979
DOI: 10.1042/cs057043s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Noradrenaline Sensitivity of Mesenteric Resistance Vessels in Spontaneously Hypertensive and Wistar—Kyoto Rats

Abstract: 1. We have compared the noradrenaline sensitivity of 150 micron arterial resistance vessels taken from a specific place in the mesenteric bed of spontaneously hypertensive (SH) rats and of control Wistar-Kyoto (WK) rats at three ages: 6 weeks, 12 weeks and 24 weeks. 2. The noradrenaline sensitivity of the vessels under normal conditions was the same at all ages in both SH and WK rats (ED50 about 3 mu mol/l). 3. After addition of cocaine (which inhibits the uptake of noradrenaline in the nerve terminals) all ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…It is reduced in the heart of older SH rats (Nykanen, Ahtee, Himberg & Paasonen, 1973;Salt & Iversen, 1973;Gudeska, Glavas, Stojanova, Petrov, Trajkov & Nikodejevic, 1976;Howe, Provis, West & Chalmers, 1979) or rats made hypertensive by adrenergic regeneration, by renal ligature of eight or salt loading (LeLorier, Hedtke & Shideman, 1976), and of renal hypertensive dogs (Lefer & Ayers, 1969); neuronal uptake is also depressed in the aorta and the kidney of DOCA-treated, salt-loaded and renal hypertensive rats, but not of the renal hypertensive dog (Lefer & Ayers, 1969;LeLorier et al, 1976;Fink & Brody, 1978). By contrast, both direct measurements of [3Hlnoradrenaline uptake and studies of the effects of inhibitors of neuronal uptake indicate that the activity of the neuronal amine pump is greater than normal in resistance vessels and arteries of the adult SH rat and of rabbits made hypertensive by partial constriction of the abdominal aorta (Bevan, Purdy, Su & Bevan, 1975;Collis & Vanhoutte, 1977, 1978aMulvany, Lajaer & Christensen, 1979;Webb & Vanhoutte, 1979;Whall, Myers & Halpern, 1980).…”
Section: Neuronal Uptakementioning
confidence: 88%
See 1 more Smart Citation
“…It is reduced in the heart of older SH rats (Nykanen, Ahtee, Himberg & Paasonen, 1973;Salt & Iversen, 1973;Gudeska, Glavas, Stojanova, Petrov, Trajkov & Nikodejevic, 1976;Howe, Provis, West & Chalmers, 1979) or rats made hypertensive by adrenergic regeneration, by renal ligature of eight or salt loading (LeLorier, Hedtke & Shideman, 1976), and of renal hypertensive dogs (Lefer & Ayers, 1969); neuronal uptake is also depressed in the aorta and the kidney of DOCA-treated, salt-loaded and renal hypertensive rats, but not of the renal hypertensive dog (Lefer & Ayers, 1969;LeLorier et al, 1976;Fink & Brody, 1978). By contrast, both direct measurements of [3Hlnoradrenaline uptake and studies of the effects of inhibitors of neuronal uptake indicate that the activity of the neuronal amine pump is greater than normal in resistance vessels and arteries of the adult SH rat and of rabbits made hypertensive by partial constriction of the abdominal aorta (Bevan, Purdy, Su & Bevan, 1975;Collis & Vanhoutte, 1977, 1978aMulvany, Lajaer & Christensen, 1979;Webb & Vanhoutte, 1979;Whall, Myers & Halpern, 1980).…”
Section: Neuronal Uptakementioning
confidence: 88%
“…Differences in the distribution of subtypes of peripheral adrenoreceptors may help explain variations in sensitivity to the hypotensive effects of drugs such as clonidine and prazosin among different species and different animal models of hypertension (Dadkar, Aroskar & Dohadwalla, 1979;Cambridge & Greengrass, 1980). The true a-adrenergic sensitivity of vascular smooth muscle from the adult SH rat and the spSH rat is augmented when compared with that from normotensive controls; however, this increased sensitivity can be masked by the more efficient disposition of noradrenaline (Clinesmidt, Geller, Govier & Sjoerdsma, 1970;Haeusler & Haefely, 1970;Hermsmeyer, 1976;Collis & Vanhoutte, 1977;Sutter & Ljung, 1977;Lais & Brody, 1978;Nagaoka, Toyoda & Iwatsuka, 1978;Berecek et al, 1979;Mulvany et al, 1979;Webb & Vanhoutte, 1979;Berecek, Schwertsshlag & Gross, 1980b;Whall et al, 1980).…”
Section: Activation Of Postjunctional Receptor Sitesmentioning
confidence: 94%
“…24 a - 42 The variability may be the result of an age factor, since the rats used in this study were still in the developmental stage of hypertension. However, Mulvany et al 43 have shown in isolated mesenteric arterial vessels (150 /Am in diameter) that the EDj,, values of NE, a measure of vascular sensitivity, did not vary within groups of SHR and WKY rats at 6, 12, and 24 weeks of age. Thus, it was of vital interest to determine if there were differences in the sensitivity of arteries to vasoconstrictors and if the elevated vascular resistance could be altered by pharmacologically changing local conditions.…”
mentioning
confidence: 99%